(untitled) (SCIENTIA JOURNAL, 2022)
Personal hygiene is a personal hyiene effort that is carried out to maintain health and enhance the level of his own health. The purpose of this study was to determine the habit of bathing, the habit of cleaning teeth, the habit of cleaning the nose, the habit of cutting nails and washing hands, the habit of wearing headgear, the habit of wearing mouth masks, and the health check. This research method is descriptive in nature to describe the application of personal hygiene of food handlers of restaurants in the work area of Puskesmas Paal V in 2019. Data taken from observations of food handlers using a checklist of the total sample of this study were 37 respondents. The results showed that personal hygiene food handlers with good bathing habits 97.29%, good teeth cleaning habits 13.51%, good nose cleaning habits 21.62%, good nail cutting habits and hand washing habits 45.95%, habit of using cover head 48.65%. The habit of using mouth masks as well as health checks does not exist. The conclusion in this study is that there are still many food handlers who are not aware of personal hygiene.